Morphofunctional changes in Leydig cells throughout the continuous spermatogenesis of the freshwater teleost fish, Serrasalmus spilopleura (Characiformes, Characidae): an ultrastructural and enzyme study - Nobrega, R. H.; Quagio-Grassiotto, I. (Springer, 2007)
The freshwater fish Serrasalmus spilopleura (piranha) has a continuous type of reproduction; gametes are constantly produced and released during the reproductive cycle. The testes do not undergo seasonal morphological changes but exhibit two constant regions throughout the year: the medullar region (involved with spermatogenesis) and the cortical region (involved with spermiation and sperm storage). We have evaluated the ultrastructure of the Leydig cells and the activity of 3 beta-HSD (an essential enzyme related to steroid hormone biosynthesis) and acid phosphatase (AcPase; lysosomal marker enzyme) in these two regions. The activity of 3 beta-HSD is stronger in the medullar region, and the Leydig cells in this region have a variety of cytological features that reflect differences in hormone synthesis and/or that could be linked to steroidogenic cells under various degrees of hormonal activity. In the cortical region, 3 beta-HSD activity is weak and the Leydig cells exhibit signs of degeneration, as confirmed by their ultrastructure and intense AcPase activity. These degenerative signs are indicative of cytoplasmic remodelling to degrade steroidogenic enzymes, such as 3 beta-HSD, that could lead to senescence or even to autophagic cell degeneration. S. spilopleura thus constitutes an interesting model for increasing our understanding of steroidogenesis control in freshwater teleost fish.
Keywords: Leydig cells; Ultrastructure; 3 beta-HSD; Acid phosphatase; Serrasalmus spilopleura; pirambeba/piranha (Teleostei)